2012
DOI: 10.1038/pr.2012.94
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction coupled with hyperglycemia: effects on cardiac structure in adult rats

Abstract: Results Growth TrajectoriesBody weight. The offspring born to pregnant rats that were fed a low-protein diet (LPD) to induce IUGR are referred to here as "LPD offspring. " Offspring born to rats that had a normal-protein diet (NPD) are referred to as "NPD offspring. " At 3 d of age, the LPD offspring had body weights (BWTs) of 4.44 ± 0.13 g which were 24% lower than the weights of NPD offspring (5.74 ± 0.16 g) (P < 0.001). At 32 wk of age, the BWTs of the LPD offspring remained significantly lower than those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
4
11
1
1
Order By: Relevance
“…These permanent alterations become detrimental when the individual is exposed to a relative overabundance of nutrients in the postnatal period, predisposing to the metabolic syndrome and type 2 diabetes mellitus, adding to the cardiovascular risk (79). In support of this hypothesis, in a rat model of IUGR, cardiac interstitial fibrosis was not only greater in growth resticted compared to AGA rats, but greatest in those growth restricted exposed to hyperglycemia, demonstrating a synergistic effect of IUGR and metabolic derangement (80).…”
Section: Postnatal Growthsupporting
confidence: 66%
“…These permanent alterations become detrimental when the individual is exposed to a relative overabundance of nutrients in the postnatal period, predisposing to the metabolic syndrome and type 2 diabetes mellitus, adding to the cardiovascular risk (79). In support of this hypothesis, in a rat model of IUGR, cardiac interstitial fibrosis was not only greater in growth resticted compared to AGA rats, but greatest in those growth restricted exposed to hyperglycemia, demonstrating a synergistic effect of IUGR and metabolic derangement (80).…”
Section: Postnatal Growthsupporting
confidence: 66%
“…Accordingly, Tintu et al (5) described the phenotype of a dilated cardiomyopathy and an increased expression of VEGF in chick embryos after hypoxia-induced IUGR. In contrast to our findings, Lim et al (7) did not detect any changes in myocardial capillarization in female IUGR rats. These conflicting data might arise from gender differences, different modes of low protein feeding, or different time points investigated.…”
Section: Impaired Myocardial Performance and Iugrcontrasting
confidence: 56%
“…At least a trend toward reduced cardiac output was also observed in another low protein model of IUGR (16). Lim et al (7) studied cardiac function in IUGR rats at an older age and in contrast to Cheema et al (8) found reduced LVEDD and normal ejection fraction. The reasons for this discrepancy remain unclear but may include different modes of low protein feeding (during pregnancy only vs. during pregnancy and lactation) and different time points investigated (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that as the LPD offspring grow older, overt cardiac dysfunction may become apparent. However, in a recent study, echocardiographic analysis in male LPD offspring at 32 weeks of age showed no evidence of cardiac dysfunction [34]; female LPD offspring were not examined in that study.…”
Section: Discussionmentioning
confidence: 96%